Kaposi’s Sarcoma-associated Herpesvirus - Novia Indriyani Adisty; Sawitri Sawitri; Willy Sandhika (Faculty of Medicine, Universitas Airlangga, 2016)
Background: Kaposi’s sarcoma (KS) revealed by Moritz Kaposi first time in 1872. In the early 1980, the prevalence of SK began to increase dramatically. A new finding leads to growth, isolation, and characterization of a novel human herpes virus, now known as Kaposi’s sarcoma-associated herpes virus (KSHV) or Human herpes virus type 8 (HHV-8) from SK lesions. Puspose: To determine the role of herpes viruses in the pathogenesis of KS. Review: KS is a cancer that develops from cells lining the lymph vessels or blood vessels. A number of KSHV encoded protein is known to have the ability to oncogenic transformation, included are latent and lytic proteins. Latent proteins tend to increase survival and proliferation of infected cells, whereas lytic viral proteins are believed to support the growth factors and angiogenic paracrine secretion useful for tumor growth and progression. Conclusion: HHV-8 is necessary, but not sufficient to cause the KS, and other factors such as immunosuppression also play a role.Key words: Kaposi’s sarcoma, herpes viruses.